Lord of the flies [videorecording (DVD)] - Aubrey, James, 1947-2010; Chapin, Tom; Edwards, Hugh, 1951-; Brook, Peter, 1925-; Golding, William, 1911-1993 (Criterion collection, 2013)
In the hands of the renowned experimental theater director Peter Brook, William Golding's legendary novel on the primitivism lurking beneath civilization becomes a film as raw and ragged as the lost boys at its center. Taking an innovative documentary-like approach, Brook shot Lord of The Flies with an off-the-cuff naturalism, seeming to record a spontaneous eruption of its characters' IDs. The result is a rattling masterpiece, as provocative as its source material.